OPTIKANING MURAKKAB MAVZULARINI O’RGANISHDA LABORATORIYA MASHG’ULOTLARINI TASHKIL QILISH - Ro‘ziyeva, D.S. (SCIENCE and SOCIETY, 2020)
The article describes an anomalous dispersion phenomenon that occurs in the dispersion liquids of the light belonging to the physics department of optics; and the effectiveness of pilot training in teaching complex subjects, such as absorption of light in the environment; and discusses the results of checking physical quantities in the experiment.
Keywords: ous dispersion anomal; dispersion; prism; refractive index; spectra; absorption of spectra; wavelength; cornerof tearing; filters